Evaluating long term properties of concrete using waste beverage glass. (2022) - Gupta, Jagriti; Jethoo, A.S.; Ramana, P.V.
Abstract: In the world, a large volume of glass (beverage, soda-lime, Toughened, float and mirror glass, etc.) is produced for utilizing in the production and manufacturing of versatile articles for harnessing in diverse activities. Out of this huge quantity of glass, a little is recycled and the rest is dumped in open lands. The study aims to produce concrete products that are environment-friendly and it also enlightens the waste glass's enhanced utilization and its application. Therefore, researchers are growing interest in using glass waste as alternative cement and aggregate construction materials. Therefore, this study characterized the replacement made for cement with the waste beverage glass for various replacements, this characterization was achieved by the produced concrete's durability properties analysis. For the substitution to cement, different ratios have been adopted by weight 0 to 40 % at 5% intervals. The influence on the mechanical (compression, flexural, and abrasion), water absorption and density, permeability, and strength loss characterization of waste glass concrete are assessed. The substitution dosages provided to the concrete of the glass perform an active role for the concrete characteristics. The experimental investigation reveals some major effects for such beverage glass waste powder replacements that it lowers the density and absorption of water. The reaction of glass waste powder and the hydroxides of calcium ie (Ca(OH)2 ) is the main reason behind the refinement of the voids, this produces the C-S-H gel termed as hydrates of calcium silicate, and this phenomenon leads to the decrement in the porosity; such reactions are pozzolanic reactions. However, the sulfate resistance of the concrete with an amount of waste glass is higher in terms of compressive strength when the sample is kept in exposer for 90 days.